The managerial Structurization of Organizations: Problems and Prospects - Butkus, Fabijonas Saulius (Ekonomika, 1997)
The object of this article is the purposeful and managerial structurization of organizations. The author, in contrary to the opinion of some management scientists proclaiming the future for organic organizations, proves the necessity of managerial structurization of ever organizations, even created for a single action. The definitions of line and staff components of organizational structure are revised. The theoretical backgrounds for the composition of line component are described in the article.